PERIODS OF WEED INTERFERENCE ON TRANSGENIC COTTON 'IMACD 6001LL' - Silva, Marcos Paulo Da; Parreira, Mariana Casari; Bressanin, Fernanda Nunes; Alves, Pedro Luis Da Costa Aguiar (Universidade Federal Rural do Semi-Árido, 2016)
ABSTRACT: The objective of this study was to determine the periods of weed interference and its impact on productivity of cotton 'IMACD 6001LL'. The experiment was conducted in Jaboticabal, São Paulo, the second crop in 2011 and consisted of two treatment groups: the first culture remained free of competing weeds since of emergence up different periods of its development: (0-15 , 0-25, 0-35, 0-45, 0-55, 0-65, 0-75 and 0-183 days - harvest). In the second treatment group was held to the contrary: the crop was in harmony with the weeds since of emergence up to the same stages of development described above. The treatments were arranged in a randomized block design in four replications. During these periods was evaluated dry matter accumulation by weeds. The cotton yield data were subjected to regression analysis and resulting in a CPWC of 35 DAE, the CPWR was 133 DAE and .The weed community was composed mainly of Raphanus raphanistrum, Amaranthus spp., Cyperus rotundus, Alternanthera tenella and Eleusine indica. Living with this community throughout the cycle resulted in reduction almost 85% in cotton yield.

RESUMO: O objetivo deste trabalho foi determinar os períodos de interferência das plantas daninhas e suas consequências na produtividade da cultura do algodão 'IMACD 6001LL'. O experimento foi realizado na safrinha 2011 e constou de dois grupos de tratamentos: no primeiro a cultura permaneceu livre da competição das plantas daninhas desde a emergência até épocas crescentes de seu ciclo de desenvolvimento: (0-15; 0-25; 0-35; 0-45; 0-55; 0-65; 0-75 e 0-183 dias - colheita). No segundo grupo de tratamento realizou-se o contrário: a cultura permaneceu em convivência com as plantas daninhas desde a emergência até os mesmos estágios de desenvolvimentos descritos anteriormente. Os tratamentos experimentais foram dispostos no delineamento em blocos casualisados, em quatro repetições. Nestes períodos foi avaliada a matéria seca acumulada pela comunidade infestante geral e específica. Os dados de produtividade do algodoeiro foram submetidos à análise de regressão resultando em um PAI de 35 dias após a emergência (DAE), o PTPI foi de 133 DAE. A comunidade infestante composta principalmente por Raphanus raphanistrum, Amaranthus spp., Cyperus rotundus, Eleusine indica e Alternanthera tenella, presente todo o ciclo da cultura acarretou em quase 85% de perda na produtividade do algodoeiro.
PERÍODOS DE INTERFERÊNCIA DAS PLANTAS DANINHAS EM ALGODOEIRO TRANSGÊNICO IMACD 6001LL
Keywords: Gossypium hirsutum; Weed; Competition; Productivity; Gossypium hirsutum; Infestantes; Competição; Produtividade.